Microbiological evaluation performed in hospital aerosolterapy equipment (Research, Society and Development, 2020)
The investigation of microbiological contamination in hospital use equipment makes it possible to assess whether the decontamination processes adopted by the health service are adequate and contribute to minimize the risks of Health Care-Related Infections. Based on this, this study aimed to evaluate the microbiological contamination of nebulizers in three health services and also to make a brief association between contamination and reprocessing methods. Ten samples of nebulizers (mask and reservoir cup) were collected, with swabs moistened with saline solution and sown in culture media selective for bacteria and fungi. After 24-48 hours of incubation at 37 °C, identification by biochemical tests of positive cultures was performed. An analysis of the health unit reprocessing protocols was also carried out. 40% of the analyzed samples presented contamination by some type of microorganism. Enterobacter sp., Gram positive bacilli and coagulase-negative Staphylococcus were the specimens found in this study. Only one Hospital, which followed the recommended for pre-washing and disinfection product, presented all its samples without microbiological contamination. Thus, it can be concluded that there is weakness in the reprocessing of these contaminated equipment, whose failures in disinfection impose risk to the user's health.